-2y-6-7y
-9y-6
I hope that this helps!
A b and 3 is the correct answer
The answer is 7 because 2 to 5 is 3 and -2 to 5 I 7
Answer:
=42x2+1
Step-by-step explanation:
6x2+36x2+12x+6
=42x2+1
Answer:
If we have a set of N elements:
{x₁, x₂, ..., xₙ}
The mean value (also called the average value) Is calculated as:
Average = (x₁ + x₂ + ... + xₙ)/n
So if x is the average of 13, -16 and 6 ( a total of 3 values)
x will be equal to:
x = (13 + (-16) + 6)/3 = (19 - 16)/3 = 3/3 = 1
x = 1
And we know that:
y = ∛8
Remember that:
2*2 = 4
and
4*2 = 8
then
2*2*2 = 2^3 = 8
then ∛8 = 2.
So we have:
y = ∛8 = 2
Now we can replace these values in the equation:
x^2 + y^3
replacing:
x = 1
y = 2
we get:
1^2 + 2^3 = 1 + 8 = 9